The Effect of Earnings, Operating Cash Flows and Accruals in Predicting Future Operating Cash Flows - Rimet, Rimet; Luthfiah, Annisa (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The purpose of this study was to analyse the effect of gross profit, operating profit, net profit, operating cash flow, changes in accounts receivable, changes in accounts payable, changes in inventory and depreciation expense simultaneously on the prediction of future operating cash flow. This research was conducted at food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) and registered from 2017 to 2019, totalling 32 companies. The sample in this study amounted to 17 companies using purposive sampling method. Data analysis using panel data regression with the help of Eviews. The results of the study explain that gross profit, operating profit, net income, changes and trade receivables have a significant effect, while operating cash flow, changes in debt, changes in inventory and depreciation expense do not have a significant effect on the prediction of future operating cash flow in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. Simultaneously gross profit, operating profit, net profit, operating cash flow, changes in accounts receivable, changes in accounts payable, changes in inventory and depreciation expense have an influence on the prediction of future operating cash flows in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period.